Private Saving in Colombia - Ortega, Juan (IMF Working Papers; Working Paper, 1998)
This paper studies the main determinants of the sharp decline in Colombia's private saving rate which accompanied the steep deterioration of the country's external current account deficit in the 1990s. The paper rejects current arguments pointing to a consumption boom and corporate behavior as the main causes of the decline. It concludes that: private consumption, explained mainly by permanent income, has only increased moderately in the 1990s; household behavior-not corporate behavior-determines private saving; and tax increases do not entirely explain the fall of private saving. Thus, reliance on external saving could be reduced by increasing public saving.